Dog with hydronephrosis due to abdominal trauma - Raposo, Talita Mariana Morata [UNESP]; Varallo, Giovanna Rossi [UNESP]; Huppes, Rafael Ricardo [UNESP]; Brum, Alexandre Martini de; Nardi, Andrigo Barboza de [UNESP] (Univ Agriculture, 2013)
Hydronephrosis is a condition that results from complete or partial obstruction of the urinary flow. This paper reports the case of a two-year-old, mixed-breed dog diagnosed with hydronephrosis of the left kidney six months after being kicked in the thoraco-abdominal region. The diagnosis was based on radiographic and ultrasonographic examinations. Percutaneous antegrade pyelography was also performed and allowed the visualization of opacification of the left kidney, which confirmed the diagnosis. Because the exams indicated that the patient had normal renal function, nephrectomy was performed. The patient remained in good health during the postoperative period and in subsequent evaluations. © 2013 PVJ.
Keywords: Canine; Kidney; Surgery